The effect of hazelnut roasted skin from different cultivars on the quality attributes, polyphenol content and texture of fresh egg pasta. (10th September 2014) - Zeppa, Giuseppe; Belviso, Simona; Bertolino, Marta; Cavallero, Maria Chiara; Dal Bello, Barbara; Ghirardello, Daniela; Giordano, Manuela; Giorgis, Marta; Grosso, Arianna; Rolle, Luca; Gerbi, Vincenzo
Abstract BACKGROUND Hazelnut skin is the perisperm of the hazelnut kernel. It is separated from the kernel during the roasting process and is normally discarded. Recent studies have reported that hazelnut skin is a rich source of dietary fibre as well as of natural antioxidants owing to the presence of phenolic compounds. The aim of this study was to assess the use of hazelnut skins obtained from different cultivars for enhancing the nutritional value of fresh egg pasta. RESULTS Skins obtained from roasted hazelnuts of four different varieties were used at three concentrations as a flour replacement in fresh egg pasta. Hazelnut skin concentration significantly influenced all evaluated physicochemical parameters as well as consumers' appreciation for the pasta, but significant differences were also observed between the four varieties. Although pasta produced with 10 and 15% hazelnut skin displayed the highest content of polyphenolic compounds and antioxidant activity in vitro, pasta containing 5% Tombul hazelnut skin showed maximum consumer preference. CONCLUSION The results obtained in the present study highlighted that it is possible to use hazelnut skin in fresh pasta production to obtain a fortified food with high fibre content and antioxidant activity. The characteristics of the resulting pasta were strictly correlated with the hazelnut variety used for skin production and, of course, with the percentage of skin that was added. © 2014 Society of Chemical Industry